PREDIKSI FAKTOR RISIKO STUNTING ANAK USIA 0-23 BULAN DI KALIMANTAN TIMUR (ANALISIS DATA SSGI 2022) - Anggraeni, Ike; Silaban, Vandy; Susanti, Rahmi; Andi Baso, Ismail; Kamaruddin, Iriyani (Magister Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2025)
Stunting is still become a major public health that causes impaired physical and cognitive growth in children, thus having a long-term impact on productivity, quality of human resources, and the country's economic growth. Data from the 2023 Indonesian Toddler Nutritional Status Survey (SSGI) shows stunting prevalence in East Kalimantan Province, with 22.8% in 2021 and 23.9% in 2022. The study aims to obtain a prediction model of stunting in children 0-23 months in East Kalimantan Province. The study used SSGI 2022 as a data source, an observational study with a cross-sectional approach, and was analyzed using binary logistic regression. The study results showed that the binary model regression model had a classification accuracy of 83.2% and could explain 59.4% of the variation in the incidence of stunting in children aged 0-23 months. The findings indicate that Low Birth Weight (LBW) and maternal height significantly affect stunting in children 0-23 months. Therefore, special attention is needed for adolescents and pregnant women through nutritional education programs to grow to optimal height and for pregnant women to give birth to healthy babies.